The Ottoman government and the Egyptian question: judicial reform and politics (1800-1914) - İnce, Mustafa. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2016., 2016)
The judicial and political relationships between Istanbul, the capital of the Ottoman Empire and Egypt as its privileged province constitute two central issues of this work. Its span covers approximately the time when the administrative bounds started to weaken as of the late eighteenth century to the outbreak of the World War I which denotes the final rupture of the relationships. Yet, in spite of the erratic nature of the bounds, the relationships between Istanbul and Egypt proceeded in an interactive process in essence. Therefore, the perspective of this work is based on the concepts of continuity-synthesizing rather than decline-fall. The province of Egypt entered the era of reform as of the early nineteenth century, which was not different from the center of the Ottoman Empire in nature. Moreover, the judicial field was among the first to be restructured in both locations. This works shows that the modernization in Egyptian judiciary is assumed to be a very significant pretext to be used on the way to independence from the Ottoman Empire by the Egyptian authorities. It sheds light on the mechanism by which Egyptian authorities could succeed in getting concessions and further privileges from the bureaucrats of the Sublime Porte. The office of the kadi of Egypt, for its capacity as to represent the sovereignty of the Ottoman sultan-caliph over Egypt at the highest level was delineated at length. Also, the attitudes of the kadis towards the reforms and the reactions of the various circles in Istanbul and Egypt against the attempts at changing the jurisdiction of the kadi court were discussed accordingly. The nature of the bounds between Istanbul as capital of the Ottoman Empire and the province of Egypt were closely related to the insufficiency of the Ottoman military power, the defeats at the battle fields and the conjuncture. The possibility of Egypt to came to the fore as an alternative encompassing power to replace the waning Ottoman authority in the Middle East. This work deals with the means of the Egyptian khedives as to gaining the status of a fully independent political actor like a sultan and their activities to become a religious leader along with the counterworks set against them.